Meningkatkan Keterampilan Menulis Teks Deskriptif melalui Metode Picture and Picture di SMPN 3 Tanjung Medan - Iskandarsyah, Iskandarsyah (EduSpirit : Jurnal Pendidikan Kolaboratif, 2024)
This study aims to improve students' descriptive text writing skills through the implementation of the Picture and Picture method at SMP Negeri 3 Tanjung Medan. The research employed a classroom action research (CAR) method with two cycles, encompassing planning, implementation, observation, and reflection stages. The subjects of this study were eighth-grade students who faced difficulties in writing effective descriptive texts. Data were collected through writing tests, observations, and questionnaires, then analyzed using both quantitative and qualitative approaches. The findings indicate that the Picture and Picture method significantly enhanced students' writing skills in terms of vocabulary, sentence structure, and fluency in composing descriptive texts. In the first cycle, students’ average scores improved compared to their initial performance, while in the second cycle, a more significant improvement was observed, with more students achieving scores above the minimum passing criteria. Furthermore, observations revealed that students were more enthusiastic and actively engaged in the learning process due to the use of visually appealing media. The questionnaire results also indicated that most students found it easier to understand descriptive text concepts through this method compared to conventional approaches. However, some challenges were encountered, such as time constraints and the need for relevant images for each topic. Therefore, careful planning and adequate media support are necessary to optimize the effectiveness of the Picture and Picture method in enhancing students’ writing skills.